2016
DOI: 10.1097/olq.0000000000000448
|View full text |Cite
|
Sign up to set email alerts
|

Results of the Women's Self-Performed Anal Pap Trial in Human Immunodeficiency Virus–Infected Women

Abstract: High-risk human papillomavirus anal infections are common in human immunodeficiency virus–infected women. We conducted a crossover study in 30 women seen in a California human immunodeficiency virus clinic, to test the feasibility of self-performed anal Pap smears. Women found the tests acceptable and feasible. Compared with physician-collected specimens, results were highly concordant for anal cytology (κ = 0.53) and high-risk human papillomavirus typing (κ = 0.59 inclusive of equivocal results, or κ = 0.81 e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…We agree that gaps in knowledge will pose significant barriers to anal cytology screening whether it be self or provider collected. In our diverse cohort of women living with HIV (WLWH) receiving healthcare in a health department setting, participants found self-collected anal cytology specimens acceptable 2 . Interestingly, there was no difference in preference between self- or clinician-performed specimen collection 2 .…”
mentioning
confidence: 91%
See 2 more Smart Citations
“…We agree that gaps in knowledge will pose significant barriers to anal cytology screening whether it be self or provider collected. In our diverse cohort of women living with HIV (WLWH) receiving healthcare in a health department setting, participants found self-collected anal cytology specimens acceptable 2 . Interestingly, there was no difference in preference between self- or clinician-performed specimen collection 2 .…”
mentioning
confidence: 91%
“…In our diverse cohort of women living with HIV (WLWH) receiving healthcare in a health department setting, participants found self-collected anal cytology specimens acceptable. 2 Interestingly, there was no difference in preference between selfor clinician-performed specimen collection. 2 As Rodriguez et al 1 highlighted, a number of factors may contribute to acceptability of self-collected specimens.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…A crossover study from 2016 with women with HIV showed that the patients found self-performed tests to be feasible, and patients have found the practice highly acceptable [ 8 ]. In addition, the quality of samples has been found comparable to that of physician-collected specimens (PCS) [ 9 ]. A cross-sectional study with HIV-negative women performed in Puerto Rico in 2012 showed that even though most women preferred having a clinician collect anal samples (61%), the acceptability of both sampling methods (self-collected vs. clinician-collected) was high [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%